An Overview of DHEA-S Levels in Chronic Stress and BMI - A Prospective Study - Tejashwini Huchannavar; Sunil Nayak; Shruthi H P; Rajesh Shenoy (RGUHS Journal of Allied Health Sciences)
Background Increased stress levels when chronic in nature may lead to diseases like hypertension cancer early ageing and fertility issues along with menstrual irregularities in females and lower sperm count in males as the age increases due to hypothalamic-pituitary-adrenal HPA axis dysregulation.Aim The aim of the present study was to assess the effect of perceived chronic stress and body mass index BMI in a subset of healthy population of male volunteers aged 18 to 45 years and female volunteers aged 18 to 40 years.Methods The selected male and female population were stratified into age and stress matched groups and one time dehydroepiandrosterone-sulfate DHEA-S levels were ascertained to evaluate any changes DHEA-S levels were measured using Chemiluminescence method within six hours of collection of the blood samples randomly collected at different time points in the day and were then statistically evaluated using Mini Tab statistical tool.Results The lower levels of DHEA-S were more pronounced in males than in females in age and stress matched stratified groups. With increasing age the fall in DHEA-S was seen in both the genders but a significant fall in DHEA-S levels was noted after the age of 35 years in males than in age matched females even when BMI was considered as a new variable in the study.Conclusion This study does not demonstrate any significant correlation between DHEA-S levels and increasing levels of perceived chronic stress and BMI in both the genders. The DHEA-S levels showed a decline with age as is a normal trend.